PENDEKATAN SUPERVISI PENDIDIKAN - Kurniati Kurniati (Universitas Islam Negeri Alauddin Makassar, 2020)
Administration and supervision are supporting tools for achieving educational goal. Likewise also the purpose of school education can also be achieved if there is a systimatic and continous administration and super vision activities. Super vision theory from perspective of the approachused begins with directive supervision. But after seeing the axxistence of supervision ineffctiveness, the directive then emerged the teory of non directive supervision. But, after seeing the existence of supervision ineffectiveness, the directive then emerged the theory of non directive supervision. The ineffectiveness of directive supervision because directive supervision does not give teachers the opportunity to develop their abilities aand creativity, full responsibility is on the supervisor, so the supervisor is dominnt. This is one of the factors behind the birth of the ssupervisor directive.